(Aflatoxins in Food Products and its methods for Elimination of the Toxin Content) - Agus Sudibyo (Warta Industri Hasil Pertanian, 2003)
Aflatoxin arehighly toxic, mutagenic, teratogenic and carcinogenic compounds that produced by species of the molds asapergillus flavus and Aspergillus parasiticus. Generally they are found in food products especially the cereals and oilseeds from the contaminated commodities during both in pre- and post harvest conditions of food production. Elimination or reduction of aflatoxins as low as possible are important in food trade concern. This paper discuss and reviews the occurrence of aflatoxin in foods commodity, methods for elimination of the toxin content by chemical, physical and biological methods and regulation of irreducible levels of aflatoxin in international trade.